CONSIDERATIONS ON AGRICULTURAL PRODUCT QUALITY MANAGEMENT - Ion CERTAN (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Global economic liberalization, progress in the means of transport, the revolution in the communication system have contributed to the acceleration of the economic value chain, including the agro-alimentary ones, in other words internationalization and globalization of human activity. We subscribe in the opinion of Ion Stanciu who states that "there are two ways to approach quality" A "and" Z ". If the quality in the "A" approach is considered a technical function, then the "Z" approach is conceptualized as a management system. This situation urges us to amplify and intensify the study of the factors influencing the quality management of agro-food products in the hope that we will suggest some proposals regarding the increase of the quality of the agro-food products and ensuring the competitiveness of the agricultural sector in the value chain specific to the conditions of internationalization and globalization of human activity.